Academic student fraud in longitudinal research design - Epanchintseva, Galina; Zubova, Lydmila; Kozlovskaya, Tatyna; Volosova, Nonna; Lebedenko, Aleksei; Bukaev, Nikolai (Journal of the University of Zulia, 2021)
The authors emphasize the importance of studying academic fraud among students. This phenomenon takes on large-scale dimensions. The authors are convinced that the solution of the problem depends on the scientific knowledge of the psychological portrait of students. Within the framework of the personalist approach, the authors present a review of the scientific literature. The authors identified a problematic field of empirical research that would reveal the dynamics of students’ subjective perceptions of a person who resorts to academic fraud. A sample of the study was formed, the author’s questionnaire was presented. The results of a longitudinal study of the dynamics of subjective perceptions of cognitive characteristics, emotional manifestations, and behavioral patterns of a student’s personality are presented for discussion. To complete the psychological portrait of the students, valid psychodiagnostic techniques were used in the study. The stages of the study are presented. The analysis of empirical data is based on the evidence-based methods of the statistical thesaurus. The findings of the study revealed the students’ ideas about the person resorting to plagiarism. In conclusion, the authors formulated step-by-step programs of psychological support for students to refuse to use various schemes of academic fraud.